tìm x\(\varepsilon\)Z biết 15x2 - 7y2=9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Để \(A\) là số nguyên thì \(\left(n+1\right)⋮\left(n-3\right)\)
Ta có :
\(n+1=n-3+4\) chia hết cho \(n-3\) \(\Rightarrow\) \(4⋮\left(n-3\right)\) \(\left(n-3\right)\inƯ\left(4\right)\)
Mà \(Ư\left(4\right)=\left\{1;-1;2;-2;4;-4\right\}\)
Suy ra :
\(n-3\) | \(1\) | \(-1\) | \(2\) | \(-2\) | \(4\) | \(-4\) |
\(n\) | \(4\) | \(2\) | \(5\) | \(1\) | \(7\) | \(-1\) |
Vậy \(n\in\left\{4;2;5;1;7;-1\right\}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(C=\dfrac{9+2\sqrt{x}}{2+3\sqrt{x}}\Rightarrow2C+3C\sqrt{x}=9+2\sqrt{x}\)
\(\Rightarrow\sqrt{x}\left(3C-2\right)=9-2C\)
\(\Rightarrow\sqrt{x}=\dfrac{9-2C}{3C-2}\ge0\Rightarrow\dfrac{2}{3}< C\le\dfrac{9}{2}\)
Mà C nguyên \(\Rightarrow C=\left\{1;2;3;4\right\}\)
- Với \(C=1\Rightarrow\sqrt{x}=\dfrac{9-2C}{3C-2}=7\Rightarrow x=49\)
- Với \(C=2\Rightarrow\sqrt{x}=\dfrac{9-2.2}{3.2-2}=\dfrac{5}{4}\Rightarrow x=\dfrac{25}{16}\)
... tương tự
C=9+2√x2+3√x⇒2C+3C√x=9+2√x
⇒√x(3C−2)=9−2C
⇒√x=9−2C3C−2≥0⇒23<C≤92
Mà C nguyên ⇒C={1;2;3;4}
- Với C=1⇒√x=9−2C3C−2=7⇒x=49
- Với C=2⇒√x=9−2.23.2−2=54⇒x=2516
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{-7\sqrt{x}+7}{5\sqrt{x}-1}+\dfrac{2\sqrt{x}-2}{\sqrt{x}+2}+\dfrac{39\sqrt{x}+12}{5x+9\sqrt{x}-2}\\ =\dfrac{-7\sqrt{x}+7}{5\sqrt{x}-1}+\dfrac{2\sqrt{x}-2}{\sqrt{x}+2}+\dfrac{39\sqrt{x}+12}{\left(5\sqrt{x}-1\right)\cdot\left(\sqrt{x}+2\right)}\\ =\dfrac{\left(-7\sqrt{x}+7\right)\left(\sqrt{x}+2\right)}{\left(5\sqrt{x}-1\right)\left(\sqrt{x}+2\right)}+\dfrac{\left(2\sqrt{x}-2\right)\left(5\sqrt{x}-1\right)}{\left(\sqrt{x}+2\right)\left(5\sqrt{x}-1\right)}+\dfrac{39\sqrt{x}+12}{\left(5\sqrt{x}-1\right)\cdot\left(\sqrt{x}+2\right)}\)
\(=\dfrac{-7x-14\sqrt{x}+7\sqrt{x}+14+10x-2\sqrt{x}-10\sqrt{x}+2+39\sqrt{x}+12}{\left(5\sqrt{x}-1\right)\cdot\left(\sqrt{x}+2\right)}\\ =\dfrac{3x+20\sqrt{x}+28}{\left(5\sqrt{x}-1\right)\cdot\left(\sqrt{x}+2\right)}=\dfrac{\left(\sqrt{x}+2\right)\cdot\left(3\sqrt{x}+14\right)}{\left(5\sqrt{x}-1\right)\cdot\left(\sqrt{x}+2\right)}=\dfrac{3\sqrt{x}+14}{5\sqrt{x}-1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)